2011
DOI: 10.1161/circulationaha.110.002139
|View full text |Cite
|
Sign up to set email alerts
|

Major Contribution of the P2Y 1 Receptor in Purinergic Regulation of TNFα-Induced Vascular Inflammation

Abstract: Background-Atherosclerosis is an inflammatory disease, and extracellular nucleotides are one of the factors possibly involved in vascular inflammation. The P2Y 1 receptor for adenosine 5=-diphosphate has been shown to be involved in the development of atherosclerosis in apolipoprotein E-deficient mice. Our aim is to determine whether the endothelial P2Y 1 receptor plays a role in leukocyte recruitment during vascular inflammation and characterize underlying mechanisms. Methods and Results-We show here that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 48 publications
1
80
1
Order By: Relevance
“…We recently reported that the P2Y 1 receptor contributes to the upregulation of adhesion molecule (P-selectin, VCAM-1 and ICAM-1) exposure in TNFα-stimulated ECs by a mechanism involving p38 MAP kinase signalling pathway, which in turn facilitates recruitment of monocytes and their transmigration. In addition, we found that the endothelial P2Y 1 receptor contributes to TNFα-induced leukocyte recruitment in experimentally inflamed arteries in a mouse model in vivo [127]. Thus, the P2Y 1 receptor might be an original target for new anti-inflammatory strategies.…”
Section: The P2y 1 Receptor As a Target For New Antiplatelet Compoundsmentioning
confidence: 81%
See 1 more Smart Citation
“…We recently reported that the P2Y 1 receptor contributes to the upregulation of adhesion molecule (P-selectin, VCAM-1 and ICAM-1) exposure in TNFα-stimulated ECs by a mechanism involving p38 MAP kinase signalling pathway, which in turn facilitates recruitment of monocytes and their transmigration. In addition, we found that the endothelial P2Y 1 receptor contributes to TNFα-induced leukocyte recruitment in experimentally inflamed arteries in a mouse model in vivo [127]. Thus, the P2Y 1 receptor might be an original target for new anti-inflammatory strategies.…”
Section: The P2y 1 Receptor As a Target For New Antiplatelet Compoundsmentioning
confidence: 81%
“…It is worthy to note that inhibition of the P2Y 1 receptor results in only moderate prolongation of the bleeding time, which could be advantageous in terms of safety. Additional advantages of targeting the P2Y 1 receptor rely on its role in vascular inflammation [127] and in atherosclerosis [128] (see below). As a consequence, this receptor could represent an attractive and original target for drugs with multiple sites of action in atherothrombosis and beyond in other inflammatory diseases.…”
Section: The P2y 1 Receptor As a Target For New Antiplatelet Compoundsmentioning
confidence: 99%
“…In addition, TNFα upregulated P2Y6 receptor expression in endothelial cells, further suggesting a direct role for purinergic signaling in this inflammation model [16]. In a separate study, endothelial cell P2Y1 receptors were shown to regulate TNFα-and IL-1β-induced adhesion molecule expression on cultured ECs and genetic ablation of P2Y1 decreased leukocyte rolling and adhesion in response to infusion of the cytokines [17]. Together, these studies point towards a direct role for purinergic receptors in promoting an inflammatory endothelial cell phenotype.…”
Section: Purinergic Control Of Vascular Inflammationmentioning
confidence: 89%
“…The effects of ATP signaling have been observed throughout the vasculature in both homeostatic and pathological conditions, including: reactive hyperemia [7,8], hypoxiainduced vasodilation [9,10], alpha-adrenergic receptor mediated vasoconstriction [11], hypertension [12], VSMC proliferation in atherosclerosis and vascular inflammation [13][14][15][16][17]. Elucidation of the mechanisms regulating purine nucleotide release in the cells comprising the vascular wall is critical for both understanding the pathogenesis of vascular diseases and the identification of novel drug interventions.…”
Section: Purinergic Signaling In the Vasculaturementioning
confidence: 99%
See 1 more Smart Citation